PENGARUH SUMBER MINERAL TERHADAP PENEKANAN Erwinia carotovora OLEH PSEUDOMONAS PENDAR-FLUOR SECARA IN VITRO - Hardian Susilo Addy . (Universitas Lampung, 2007)
Antimicrobial Stimulation of Fluorescent Pseudomonad to Inhibit Soft-rot Pathogen Caused by Erwinia carotovora subsp. Carotovora. This research was conducted to study effect of mineral sources on inhibition Erwinia carotovora by fluorescent pseudomonad. We used several mineral sources to stimulate antimicrobial substances from fluorescent pseudomonad that responsible to inhibit E. carotovora subsp. carotovora in vitro. The results showed that zinc 0,5 mM were the best to increase antagonistics of fluorescent psudomonad againts E. carotovora. Zinc were increased antimicrobial substances twohold compared with control without stimulant agent. Detection of antimicrobial substance using TLC showed that only one antimicrobial was detected with retention factor (Rf) of 0,68 – 0,72. However, identification and characterization of that substance is still needed.